PENERAPAN METODE DEMONSTRASI DALAM UPAYA MENINGKATKAN PEMAHAMAN KONSEP TERHADAP OPERASI PERKALIAN BILANGAN MELALUI MEDIA BENDA KONGKRIT SISWA KELAS IV SD NEGERI SLAWI KULON 06 KABUPATEN TEGAL - Kusumawati, Noviana (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The purpose of this action research is to improve mathematics teaching fourth grade students on multiplication operation on numbers, especially in improving the ability of understanding the concept of students and increase student activity in mathematics learning activities. This study was conducted in three phases, namely the pre cycle, the first cycle and second cycle. From the results of the pre-cycle observation data showed that the average results of the achievement test scores of understanding the concept of the ability of each individual student is 60.9 with a completion percentage of the value of 52.63 %. In the first cycle, an increase in the average achievement score is 72.4 with the percentage of completion value of 76.32 %. The results of the study have not been able to reach an optimal mastery of KKM was set at 60. After the improvement of learning through observation and reflection on the first cycle, obtained student learning outcomes in second cycle increased significantly to an average of comprehension achievement test scores to the concept reached 78.5 completion percentage value of 94.47 %. The conclusion that the improvement of learning by demonstration method through the medium of concrete objects can improve student learning outcomes in the ability of understanding mathematical concepts of multiplication operation on the material number. Kata Kunci:Concept Comprehension of Ability, Demonstration Method, Media of Concrete Objects.